Efektivitas Antibakteri Ekstrak Jamur Endofit BS pada Media Tumbuh Beras Merah - Pramesti, Radia Sagita; Iryani, Iryani; Ulfah, Mariam (Periodic, 2024)
BS endophytic fungus is a fungus isolated from the flower of the bitter plant (A. paniculata) which is known to produce various secondary metabolites which are reported to have antibacterial bioactivity. The purpose of this study was to determine the antibacterial activity of the extract of the endophytic fungus BS isolated from the bitter flower (A. paniculata) on brown rice growing media against Streptococcus mutans, Staphylococcus aureus, and Pseudomonas aeruginosa bacteria. BS endophytic fungi were grown on brown rice media and then extracted by maceration method with ethyl acetate as solvent. The antibacterial activity test of the extract was carried out by disc diffusion method. The results showed that BS endophytic mushroom extract grown on brown rice media could inhibit the growth of Streptococcus mutans, Staphylococcus aureus, and Pseudomonas aeruginosa bacteria at concentrations of 10%, 30%, and 50%. In conclusion, BS endophytic fungus isolated from A. paniculata flower can inhibit the growth of bacteria with the smallest diameter inhibitors successively on Staphylococcus aureus, Streptococcus mutans, Pseudomonas aeruginosa bacteria